PENERAPAN STRATEGI THINK TALK WRITE DALAM MODEL PEMBELAJARAN KOOEPRATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII3 SMP NEGERI 25 PEKANBARU - Afriyanti, Nadya; Angraini, Rini Dian; Saragih, Sehatta (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is conducted based on mathematics learning outcomes of class VIII3 students of state Junior High School 25 Pekanbaru which is still under KKM (Minimum Criteria of mastery learning) that has been settled by the school that is 75. This approach of this research is classroom action research with 2 cycles. The subjects of the study were students of class VIII3 SMPN 25 Pekanbaru consisting of 15 male students and 27 female students with heterogeneous ability. This research was conducted on 28 April 2016 until 23 May 2016. The data in this study were obtained from the observations of teacher and student activity and student outcomes by analyzing qualitatively and quantitatively. Based on the data analysis of teacher and student activity after implementing a Think Talk Write strategy in cooperative learning, teacher and student activities are done well and experienced improvement at each meeting. Based on the data analysis of student learning outcomes, there is an increase in student learning outcomes in each cycle. Based on the analysis of KKM achievement, the number of students who reached KKM at UH 1 amounted to 35 people with percentage 83,3 % and UH 2 amounted to 39 people with percentage 90,48 %. Based on the analysis of frequency distribution, there is an increase in the number of students who get very high criteria and the decrease in the number of students who get enough and low criteria. From this study can be concluded that the implementation Think Talk Write strategy in cooperative learning approach can improve the learning process and also to remind students of mathematics learning outcomes of VIII3 students of state Junior High School 25 Telekomunikasi Pekanbaru even semester of academic year 2015/2016 at KD 5.2 Making cube nets, beams, prisms and pyramids and on KD 5.3 Calculate surface area and volume cubes, beams, prisms and pyramids.Key words: Mathematics learning outcome, Cooperative learning, Think Talk Write